Respuesta :

STEP 1: Multiply second equation by -3.

After multiplying we have the following system:

3x+4y−3x+3y=8=−36

STEP 2: add the two equations together to eliminate x from the system.

7y=−28

STEP 3: find y

y=−4

STEP 4: substitute the value for y into the original equation to solve for x.

3x+4(−4)=8

x=8

Answer: D. (8, -4)

Step-by-step explanation:

3x + 4y = 8 --------------(1)

x - y = 12--------------(2)

eqn(2) × 3

3x - 3y = 36-----------(4)

eqn(4) - eqn(1)

-7y = 28

Divide bothside by -7

y = -4

Again, multiply eqn(2) by 4

4x - 4y = 48 ---------------(5)

eqn(5) + eqn(1)

7x = 56

Divide bothside by 7

x = 8

Therefore x=8 and y=-4

ACCESS MORE